PUBLIC CONSULTATIONS AND EXPERTISE: DEMARCATION OF INSTRUMENTS AND PROBLEMS OF APPLICATION IN UKRAINE - Біденко, Ю. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
Public consultations and public expertise are considered as tools of citizens' influence on the formation and implementation of public policy. Political participation depends not only on the qualities of civil society or the elite, but also on the instruments available for сivic inclusion in decision-making process. In the European Union, special tools for consultations and initiatives have been implemented, while in Ukraine they are not systematized and concern only certain authorities. The demarcation between public consultations and civil expertise was conducted in the political and legal context, as well as the areas and subjects of the initiative were described. Based on  the practicticies of public consultations and expertise in Ukraine some recommendations on their functional and substantive empowermet were provided by the author.